The Association between Motivation and Sanction on Hand Hygiene Compliance among Nurses at Dr. Pirngadi Hospital, Medan, North Sumatera - Simanjuntak, Sondang; Yustina, Ida; Zulfendri, Zulfendri (Journal of Health Policy and Management, 2019)
Background: Hand hygiene is an effective behavior to prevent infection among health workers. This study aimed to determine the associations of motivation and sanction on hand hygiene compliance among health workers at Dr. Pirngadi Hospital.Subjects and Method: A cross-sectional study was conducted at Dr. Pirngadi Hospital, Medan, North Sumatera, Indonesia. A sample of 33 health workers was selected for this study by total sampling. The dependent variable was hand hygiene obedience. The independent variables were sanction and motivation. The data were collected by questionnaire and analyzed by multiple logistic regression.Results: Hand hygiene compliance was associated with the presence of sanction (OR= 3.44; 95% CI= 1.22 to 4.95; p= 0.041) and motivation (OR= 4.77; 95% CI= 2.52 to 6.30; p= 0.029).Conclusion: Hand hygiene compliance is associated with sanction and motivation. Keywords: hand hygiene, compliance, sanction, motivationCorrespondence: Sondang Simanjuntak. Masters Program in Public Health, Universitas Sumatera Utara, Jl. Universitas 21, Medan 20155, North Sumatera, Indonesia. Email: sondangstarlyn@gmail.comJournal of Health Policy and Management (2019), 4(2): 91-95https://doi.org/10.26911/thejhpm.2019.04.02.03